2020
DOI: 10.1136/bmjopen-2020-038314
|View full text |Cite
|
Sign up to set email alerts
|

Codesigning discharge communication interventions with healthcare providers, youth and parents for emergency practice settings: EDUCATE study protocol

Abstract: IntroductionDischarge communication is an important aspect of patient care but frequently has shortcomings in emergency departments (EDs). In a paediatric context, youth or parents with young children often leave the ED with minimal opportunity to ask questions or to ensure comprehension of important information. Strategies for improving discharge communication have primarily targeted patients and/or parents, although neither group has been engaged in intervention design or implementation. Furthermore, ED heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…There may be concerns about placing service users, family members, and clinicians in the same group as service users may feel uncomfortable speaking up. However, previous research has shown that forming a heterogeneous co-design team with patients and clinicians can be done well [113][114][115][116]. Furthermore, the CAMH Lived Experience Advisory Group supported this as an effective approach for reaching a consensus.…”
Section: Anticipated Challenges and Mitigation Strategiesmentioning
confidence: 99%
“…There may be concerns about placing service users, family members, and clinicians in the same group as service users may feel uncomfortable speaking up. However, previous research has shown that forming a heterogeneous co-design team with patients and clinicians can be done well [113][114][115][116]. Furthermore, the CAMH Lived Experience Advisory Group supported this as an effective approach for reaching a consensus.…”
Section: Anticipated Challenges and Mitigation Strategiesmentioning
confidence: 99%
“…Shortly after Boivin et al’s 2018 systematic review was published, 14 the Patient Engagement In Research Scale (PEIRS) was published as the first tool designed to measure the degree of meaningful patient engagement in research on project teams 16 . The PEIRS is based on an empirical conceptual framework enhanced with a literature review, 5 recognized as a promising and important tool for the evaluation of patient and family caregiver engagement in research 13,17‐20 . The framework outlines the key components of and defines meaningful patient engagement in research as the planned, supported and valued involvement of patients in the research process, which facilitates their contributions and offers a rewarding experience 5 .…”
Section: Introductionmentioning
confidence: 99%
“…16 The PEIRS is based on an empirical conceptual framework enhanced with a literature review, 5 recognized as a promising and important tool for the evaluation of patient and family caregiver engagement in research. 13,[17][18][19][20] The framework outlines the key components of and defines meaningful patient engagement in research as the planned, supported and valued involvement of patients in the research process, which facilitates their contributions and offers a rewarding experience. 5 While the original 37-item PEIRS has undergone face and content validation, most of its measurement properties have not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Parents/caregivers have also reported wanting information on how to help their child deal with the next crisis and how to support themselves [8]. Past research has indicated, however, that 32-48% of families do not receive any discharge instructions [4], and if instructions are provided, they are often brie y explained with crucial details missing [12], and may not be well understood by patients or parents/caregivers [8,11].…”
mentioning
confidence: 99%
“…Despite the signi cant role that parents/caregivers, pediatric patients, and health care providers play in the discharge communication process, they have not been involved in developing discharge interventions [12]. The involvement of children/adolescents and parents/caregivers in the development of discharge inventions for mental health care could improve access to treatment and services after the ED visit and increase the quality and appropriateness of discharge interventions provided in the ED [13,14].…”
mentioning
confidence: 99%